Tuberculosis and co-infection with HIV-AIDS its history, cause and spread - Singh, Pranveer (Cambridge Scholars Publisher, 2019)
This book deals with Tuberculosis in exhaustive detail. It incorporates the most recent research on the disease, and is divided into different sections highlighting the chronological history of its development, global spread, the current scenario in India with regards to the disease, seasonality, co-infection with HIV-AIDS, and the novel combinatorial-therapy with special reference to underprivileged and tribal populations. Avoiding lengthy and irrelevant descriptions, it will help the reader, particularly students, to grasp the facts.